Improving Library Services: A Web-Based Solution for Jember Regency Prosecutor's Office - Fitriana, Dina Ayu; Wardoyo, Ari Eko; Azizah, Habibatul (Jurnal Pendidikan Informatika (EDUMATIC), 2024)
In the era information technology advancement, adaptation and integration of technology have become essential needs for organizations across various sectors. This research endeavors to design and implement an efficient and modern web-based library system to the specific needs of the Jember Regency Prosecutor's Office. This study employs structured analysis to comprehensively understand existing library management processes, and it adopts the waterfall model for system development. This model entails sequential stages, including requirement analysis, system design, implementation, and testing using black box method, ensuring a systematic approach to system development. Data collection techniques involve interviews with key stakeholders and examination of existing systems and processes. Data analysis encompasses identifying challenges and requirements, which inform system design and development. The findings indicate that the newly developed web-based library system effectively addresses identified challenges, streamlining administrative processes and enhancing user experience. Its successful implementation is expected to significantly improve operational efficiency and resource accessibility at the Jember Regency Prosecutor's Office library, contributing to the modernization of library services in Indonesia and paving the way for future advancements in library technology development.